Artificial Intelligence (AI) in English Writing Skills Learning: A Systematic Review - Wiwiek Zulfiani Rahman (ETDC: Indonesian Journal of Research and Educational Review, 2026)
AI has rapidly changed English Language Teaching (ELT), notably writing skills. AI has enormous potential, but educators and academics still struggle with its ethical use, over-reliance, and integration into an organized curriculum. This project will thoroughly review AI integration in English writing skills learning. It examines the most used AI technologies, their efficacy in improving writing, and their pedagogical implications. A Systematic Literature Review (SLR) was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were synthesized from peer-reviewed articles published between 2023 and 2026 across major databases, including Scopus, Web of Science, and Google Scholar. A total of [35] pertinent studies were chosen according to stringent inclusion and exclusion criteria. The findings indicate that AI tools, including Automated Writing Evaluation (AWE) systems, Large Language Models (LLMs) such as ChatGPT, and intelligent grammar checkers (e.g., Grammarly), significantly enhance writing accuracy, coherence, and student motivation by delivering prompt, individualized feedback. However, the review also identifies critical issues, including concerns over academic integrity, potential algorithmic bias, and a "dependency trap" where students may prioritize AI output over the development of their voice. This paper presents a complete framework for educators and policymakers to responsibly integrate AI into writing teaching. The area benefits from perceiving AI as a "collaborative partner" in the writing process rather than a "correction tool" and recognizing the importance of digital literacy and ethical principles in modern English classrooms.